Sea turtles in the eastern margin of the North Atlantic: the northern Ibero-Moroccan Gulf as an important neritic area for sea turtles - BELLIDO LÓPEZ, JUAN JESÚS; TORREBLANCA, ESTEFANIA; BAEZ, JOSÉ CARLOS; CAMIÑAS, JUAN ANTONIO (Mediterranean Marine Science, 2018)
This study summarizes nearly 20 years (1997-2015) of tracking strandings of sea turtles along the Andalusian coast. In this period 2495 specimens were recorded, most of them loggerhead turtles Caretta caretta (92.6%) and leatherback turtles Demochelys coriacea (7.1%). Two other species were almost insinificant, green turtle Chelonia mydas (0.2%) and Kemp’s ridley Lepidochelys kempi (0.1%). Significant part of the turtles were recorded in the Atlantic coast, although in this area the incidence of alive specimens was low. Spring and summer were the seasons with more specimens stranded, probably related to warmer and more productive waters. The size of the loggerhead turtles observed highlights an important presence of inmature specimens in Andalusian waters, although mature individuals were not rare. In the case of leatherback turtles, adult stage is the only detected in the specimens recorded. These results, combined with the fact that the Atlantic coast has a large continental shelf and a high primary productivity near the coast, suggesting that the gulf of Cádiz may represent a neritic habitat used by the sea turtles. In this case, new and more effective politics of conservation are needed in order to protect sea turtles in this area.